A feasibility study of Lactobacillus plantarum in fruit powders after processing and storage. (3rd November 2015) - Borges, Sandra; Barbosa, Joana; Silva, Joana; Gomes, Ana M.; Pintado, Manuela; Silva, Cristina L. M.; Morais, Alcina M. M. B.; Teixeira, Paula
Summary: The aim of this study was to develop fruit powders (apple, banana and strawberry) enriched with a probiotic strain ( Lactobacillus plantarum 299v). Two methodologies were proposed: (i) drying of the fruit with probiotic culture incorporated (by convection) or (ii) drying of fruit (by convection) and addition of spray‐dried probiotic culture. In the first methodology, processing caused a notable reduction in probiotic viable counts in apple, but this reduction was lower during drying of banana and strawberry. A large reduction in viable cells was also recorded during storage. In the second methodology, the survival of L. plantarum 299v was considerably higher during spray‐drying, and fruit powders with a microbial content suitable for a probiotic food (10 8 –10 9  cfu g −1 ) were obtained. The fruit powders incorporating L. plantarum 299v can be stored at 4 °C or at room temperature, for at least 3 months. This preliminary study demonstrated that fruit powders are good carriers of probiotic cultures, but the techniques used to produce them should be carefully considered. Abstract : Methodologies used to obtain a fruit powder with Lactobacillus plantarum : (A) drying of the fruit with probiotic culture incorporated (by convection) and (b) drying of fruit (by convection) and addition of spray‐dried probiotic culture.